Proceedings of International Conference on Robotics and Automation
DOI: 10.1109/robot.1997.620121
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic simulation of virtual mechanisms with haptic feedback using industrial robotics equipment

Abstract: This paper explores using industrial robotics equipment in a haptic (or kinesthetic) force display system conceived for mechanism design applications. The dynamics and kinematics of an aircraft jlight control columrhvheel are simulated as a human interacts directly with the end effector of a commonly available robotic manipulator. An admittance control paradigm is used for developing a haptic system wherein realistic simulation of the dynamic interaction forces between a human user and the simulated virtual ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…We can also observe that SDVAC-C did not outperform SDVAC. Due to the complexity of human body dynamics during walking as well as the heuristic nature of SDVAC-C in (22), it is a challenging task to quantitatively understand this phenomenon. However, empirically, the human users reported that SDVAC-C was "too active" and prone to "overshoot".…”
Section: Humanmentioning
confidence: 99%
“…We can also observe that SDVAC-C did not outperform SDVAC. Due to the complexity of human body dynamics during walking as well as the heuristic nature of SDVAC-C in (22), it is a challenging task to quantitatively understand this phenomenon. However, empirically, the human users reported that SDVAC-C was "too active" and prone to "overshoot".…”
Section: Humanmentioning
confidence: 99%
“…Even industrial robots fitted with a force sensor, can be used as haptic devices. (11) However, the performance in rendering low mass is typically not good as it requires high accelerations and speed from the device which can not always be realized. A nice example of an admittance controlled commercially available haptic device is the HapticMaster.…”
Section: Journal Of Advanced Mechanical Design Systems and Manufactmentioning
confidence: 99%
“…However, the effect of these dynamics can be significantly reduced through the use of active control, enabling the successful implementation of manipulators in a variety of applications. Some examples of this approach include manipulators used as driving and flight simulators [17][18] and mass simulators for extravehicular training [19].…”
Section: Large-scale Hapticsmentioning
confidence: 99%